2005
DOI: 10.4049/jimmunol.174.5.2951
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk-Derived Antigen-Specific CD8+ T Cells: An Extralymphoid Effector Memory Cell Population in Humans

Abstract: Although mouse studies have demonstrated the presence of an effector memory population in nonlymphoid tissues, the phenotype of human CD8+ T cells present in such compartments has not been characterized. Because of the relatively large number of CD8+ T cells present in breast milk, we were able to characterize the phenotype of this cell population in HIV-infected and uninfected lactating women. CMV, influenza virus, EBV, and HIV-specific CD8+ T cells as measured by the IFN-γ ELISPOT and MHC class I tetramer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
56
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 51 publications
12
56
0
Order By: Relevance
“…Breast milk CD4+ T cells express high levels of CCR5, indicating an activated phenotype [282]. Similarly, milk CD8+ T cells belong to an effector memory population, and express activation markers [284]. Consistent with this, the CD8+ T cells possess CTL function [281], and the relative magnitude of the CTL response is much higher than in blood, suggesting that there is selective transportation of these cells into breast milk [283].…”
Section: Mastitismentioning
confidence: 73%
“…Breast milk CD4+ T cells express high levels of CCR5, indicating an activated phenotype [282]. Similarly, milk CD8+ T cells belong to an effector memory population, and express activation markers [284]. Consistent with this, the CD8+ T cells possess CTL function [281], and the relative magnitude of the CTL response is much higher than in blood, suggesting that there is selective transportation of these cells into breast milk [283].…”
Section: Mastitismentioning
confidence: 73%
“…From there, they are believed to enter the lumen of alveoli via the paracellular pathway (7). Functional studies have demonstrated differences between breast milk and blood leukocytes, where breast milk T cells and macrophages appear to be more motile than their blood counterparts (57)(58)(59)(60)(61), suggesting a selective migration of leukocytes from the maternal circulation into milk (62) and/or selective alterations of leukocyte properties while in the breast. This may be important for their upcoming transfer to, safety, and/or function in the infant.…”
Section: The Breast Milk Leukocytementioning
confidence: 99%
“…67 Breast milk T cells differ both in relative abundance and quality when compared to the T cells found in peripheral blood. 68 The largest proportion of TCD8 + TCRgd + (expressing L-selectin, integrin α4β7, MAdCAM-1) compared with the blood suggests that these cytotoxic T cells (CD8 + ) carry out selective homing from the mucosal immune system to the mammary gland.…”
Section: Breast Milk Cellsmentioning
confidence: 99%